Treasures of Irish Christianity Volume 2 : A People of The Word - Salvador Ryan; Brendan Leahy 1960- (Ireland Veritas Publications, 2013)
"This second, richly illustrated volume [...] offers readers further scholarly yet accessible essays on a vast array of treasures from the Irish Christian tradition; this time, with a focus on the Irish and their relationship to the Word. The contributions, from a wide range of Irish scholars, cover topics from religious folk tales to reflections on Yeats, Kavanagh and Beckett; from annotations on ancient manuscripts to the first Lutheran congregation in Dublin; from early High Crosses to the thirteenth-century Kilcormac Missal; from the medieval Office of St Brigit to Pugin architecture; and from Church of Ireland hymnody to the recent Share the Good News publication." Front flap.
Keywords: History of Christianity (3JGQjN GdeSjMjIs; Christianity -- Ireland; Christianity and culture -- Ireland; Language and languages -- Religious aspects -- Christianity